2017
DOI: 10.4172/2169-0022.1000318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Shear Connection on Strengthened Composite Beams with Externally Post-Tension Tendons

Abstract: Composite steel-concrete beams are used widely in bridges and buildings construction as the main structural elements in flexure. These structures have a design life and this may be reduced if loads are increased or environmental degradation could happen. These changes may reduce the design life and strength of such members and thus replacement or retrofitting may need to be considered. The present study focuses on evaluating the effect of partial shear connection on strengthen composite beams with externally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Furthermore, some research programs within the past experience of this field proved that the partial interaction theory of shear connectors gives high deflection levels if compared with full interaction as cited by EL-Shihy et al [11]. The current study tries to examine the full and partial interactions Al-Sabtea Bridge by implementing numerical modelling using finite element software "ANSYS".…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, some research programs within the past experience of this field proved that the partial interaction theory of shear connectors gives high deflection levels if compared with full interaction as cited by EL-Shihy et al [11]. The current study tries to examine the full and partial interactions Al-Sabtea Bridge by implementing numerical modelling using finite element software "ANSYS".…”
Section: Introductionmentioning
confidence: 93%
“…The analysis results indicated that the grade of concrete embedment significantly decreases the prototype ultimate shear force, relative slip and shear toughness. EL-Shihy et al, [14] studied the effects of partial interaction of shear connectors on the performance and strength of composite beams by finite elements approach. The analysis results indicated that the partial interaction theory gave increased in deflections and stresses as compared with the full interaction performance.…”
Section: Introductionmentioning
confidence: 99%